2019
DOI: 10.1136/bmjopen-2018-023447
|View full text |Cite
|
Sign up to set email alerts
|

Dog ownership and cardiovascular risk factors: a nationwide prospective register-based cohort study

Abstract: ObjectiveTo study the association between dog ownership and cardiovascular risk factors.DesignA nationwide register–based cohort study and a cross-sectional study in a subset.SettingA cohort of 2 026 865 participants was identified from the Register of the Total Population and linked to national registers for information on dog ownership, prescribed medication, hospital admissions, education level, income and country of birth. Participants were followed from 1 October, 2006, to the end of the study on 31 Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We did not have information about the breed, age, and pedigree of dogs, which may moderate the association between dog ownership and health outcomes, including sleep. For instance, owning a dog of mixed pedigree or a dog belonging to the 'companion/toy' breed group was associated with hypertension and dyslipidemia in the dog owner 13 . Additionally, owning a dog from the 'Spitz/primitive' breed and the combined group of ' active dog breeds' was associated with a lower risk of diabetes mellitus 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not have information about the breed, age, and pedigree of dogs, which may moderate the association between dog ownership and health outcomes, including sleep. For instance, owning a dog of mixed pedigree or a dog belonging to the 'companion/toy' breed group was associated with hypertension and dyslipidemia in the dog owner 13 . Additionally, owning a dog from the 'Spitz/primitive' breed and the combined group of ' active dog breeds' was associated with a lower risk of diabetes mellitus 13 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, owning a dog of mixed pedigree or a dog belonging to the 'companion/toy' breed group was associated with hypertension and dyslipidemia in the dog owner 13 . Additionally, owning a dog from the 'Spitz/primitive' breed and the combined group of ' active dog breeds' was associated with a lower risk of diabetes mellitus 13 . Altogether, our study does not provide compelling evidence for the hypothesis that dog walking may result in overall better sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Research on large datasets or with more objective measures than questionnaires repeatedly fails to confirm the supposed benefits (reviewed in (83,84). Dog owners do not live longer (85), do not recover better after a heart attack (86), their blood pressure is not lower, or it is even slightly higher than non-dog owners (87,88), they are not more healthy (89), not less obese, not more active (90), not happier (83), do not commit suicide less often (91)(92)(93), are not less lonely (81), or less depressed, but may be more depressed (94,95). They can face unique difficulties specifically related to caring for dogs.…”
Section: Figure 5 the Potential Costs And Benefits Of Pet Dog Keeping...mentioning
confidence: 99%
“…However, a meta-analysis of 11 studies found that persons with a pet had a 1.7 mmHg (95% CI : − 3.062 to − 0.310 mmHg) lower systolic BP (SBP), a non-significant reduction in diastolic BP (DBP) [mean diastolic BP = − 0.23 (95% CI : − 1.05 to 0.60)], and a significant decrease in HR of 2.3 bpm (95% CI : − 3.074 to − 1.573 bpm) [ 5 ••]. The BP lowering effect was especially evident during direct contact with the pet [ 10 ], and influenced by the intesity of the owner-pet relationship [ 11 ], species of the pet [ 9 ••, 12 ] and breed of dog [ 13 ].…”
Section: Pet Ownership and The Risk Of Hypertensionmentioning
confidence: 99%